Modulation of Colorectal Tumor Behavior via lncRNA TP53TG1-Lipidic Nanosystem - Farimah Masoumi; Sofia M. Saraiva; Belén L. Bouzo; Rafael López-López; Manel Esteller; Ángel Díaz-Lagares; María de la Fuente (MDPI AG, 2021)
Long non-coding RNAs (lncRNAs) are an emerging group of RNAs with a crucial role in cancer pathogenesis. In gastrointestinal cancers, TP53 target 1 (TP53TG1) is an epigenetically regulated lncRNA that represents a promising therapeutic target due to its tumor suppressor properties regulating the p53-mediated DNA damage and the intracellular localization of the oncogenic YBX1 protein. However, to translate this finding into the clinic as a gene therapy, it is important to develop effective carriers able to deliver exogenous lncRNAs to the targeted cancer cells. Here, we propose the use of biocompatible sphingomyelin nanosystems comprising DOTAP (DSNs) to carry and deliver a plasmid vector encoding for TP53TG1 (pc(TP53TG1)-DSNs) to a colorectal cancer cell line (HCT-116). DSNs presented a high association capacity and convenient physicochemical properties. In addition, pc(TP53TG1)-DSNs showed anti-tumor activities in vitro, specifically a decrease in the proliferation rate, a diminished colony-forming capacity, and hampered migration and invasiveness of the treated cancer cells. Consequently, the proposed strategy displays a high potential as a therapeutic approach for colorectal cancer.